Vibration Analysis and Optimization Design of Vane Compressor Discharge Valve for Car Air Conditioner - Li Chunyin; Wang Shulin (Zhileng xuebao)
By analyzing the motion of vane compressors for car air conditioner we proposed a mathematical model for the vibration of the discharge valve and determined its natural frequencies and mode shape in combination with the calculation using UG NX Nastran software. We show that the refrigeration efficiency can be maxima when the valve sheet takes the optimized thickness of 0.305 mm based on the vibration analysis. At the same time, test results revealed that the discharge flow pulsation and system noise are effectively controlled, and the both are lower than the upper limit of the "GMW Standard" of the U.S. General Motors Corporation. The study may be significant to enhance the refrigeration efficiency of the system and reduce discharge flow pulsation and noise of vane compressors.